Virulence factors of Streptococcus anginosus – a molecular perspective - Kuryłek, Aleksandra; Stasiak, Monika; Kern-Zdanowicz, Izabela (Frontiers in Microbiology, 2022)
Streptococcus anginosus together with S. constellatus and S. intermedius constitute the Streptococcus anginosus group (SAG), until recently considered to be benign commensals of the human mucosa isolated predominantly from oral cavity, but also from upper respiratory, intestinal, and urogenital tracts. For years the virulence potential of SAG was underestimated, mainly due to complications in correct species identification and their assignment to the physiological microbiota. Still, SAG representatives have been associated with purulent infections at oral and non-oral sites resulting in abscesses formation and empyema. Also, life threatening blood infections caused by SAG have been reported. However, the understanding of SAG as potential pathogen is only fragmentary, albeit certain aspects of SAG infection seem sufficiently well described to deserve a systematic overview. In this review we summarize the current state of knowledge of the S. anginosus pathogenicity factors and their mechanisms of action.